PENGARUH IMPLEMENTASI DANA PEMBERDAYAAN MASYARAKAT TERHADAP EFEKTIVITAS PENANGGULANGAN KEMISKINAN DI KECAMATAN BAKAUHENI KABUPATEN LAMPUNG SELATAN - MALIK Malik (e-JKPP, 2016)
Influence of Implementation of Fund of Society Enableness To Effectiveness of overcoming Poorness In Subdistrict of Bakauheni Regency Float the South archProblem of this research is : (1) What Implementation of Fund of Society Enableness have an effect on to Effectiveness of overcoming Poorness In Subdistrict of Bakauheni Regency Float the South arch, (2) How big influence of Implementation of Fund of Society Enableness to Effectiveness of overcoming Poorness In Subdistrict of Bakauheni Regency Float the South arch.Research Method which is according to researcher as according to this research method is use the this research type is explanatory survey. Research population as much 510 group of family of receiver of Implementation of Fund of Enableness of Regency Society Float the South arch. By utilizing formula opened by Riduan (2004:5) hence sum up the sampel determined by as much 60 people.Result of research indicate that there is Influence of Implementation of Fund of Society Enableness to Effectiveness of overcoming Poorness In Subdistrict of Bakauheni Regency Float the South arch, biggest influence from variable of maker of Implementation of Fund of Society Enableness that is organizational dimension of executor of equal to 69.72, while smallest dimension from variable of maker of Implementation of Fund of Society Enableness is ideal policy dimension that is equal to 64.86. contribution of Variable of Implementation of fund of society enableness to effectiveness of penanggulangan poorness be at the category enough. The mentioned happened by because Implementation of fund of society enableness conducted by not yet full according to rule which have been determined, so that uncommitt optimally.